Enhancing Students' Self-Regulated Learning through Differentiated Instruction Based on Prior Knowledge - Muhammad Idris Hasanuddin; Zuhdiah Zuhdiah; Sukri Badaruddin; Aan Setiawan; Ummi Kalsum (LP. Ma'arif Janggan Magetan, 2024)
Differentiated instruction, which tailors learning experiences based on students’ readiness, interests, and prior knowledge, has been identified as an effective approach to fostering self-regulated learning. This study aims to analyze the impact of differentiated instruction based on prior knowledge on students' self-regulated learning, focusing on its benefits, challenges, and potential solutions for effective implementation. A systematic literature review was conducted using major academic databases, applying PRISMA guidelines for article selection. Thematic analysis was employed to identify key themes related to prior knowledge, differentiated instruction, and self-regulated learning. The findings indicate that differentiated instruction based on prior knowledge positively contributes to the development of students' self-regulated learning, metacognitive skills, self-efficacy, and intrinsic motivation. However, challenges such as limited teacher training, time constraints, and lack of institutional support hinder its implementation. Various strategies, including professional learning communities (PLCs), dynamic assessment, and adaptive technology, have been proposed to address these issues. The study concludes that strengthening teacher training programs, fostering collaboration among educators, and leveraging technology are essential to optimizing the implementation of differentiated instruction based on prior knowledge. Future research should explore its application across different educational levels and subject areas to enhance its effectiveness in diverse learning contexts.